Calculo

Solo disponible en BuenasTareas
  • Páginas : 2 (291 palabras )
  • Descarga(s) : 0
  • Publicado : 1 de noviembre de 2011
Leer documento completo
Vista previa del texto
87) limx→1x-1senx3-1
limx→1x-1senx3-1 x2+x+1x2+x+1
limx→1x3-1sen(x3-1)(x2+x+1)
limx→11senx3-1x3-1(x2+x+1)11(1+1+1)=1/3

88) limx→0ex-1-xx(ex-1)
Derivando limx→0ex-1ex-1+xex
Derivando limx→0exex-1+xex
limx→0ex (1)ex(2+x =1/2
89)limx→01-cosxx sen x
limx→0senxsen x+xcosx
limx→0cosx cosx+cosx-xsenx
11+1-0=12
90) limx→0x arcsen xx-sen x
limx→0arcsenx+ x (11- x2x-cos x
limx→011- x2+ 11- x2+ x(-121-x2-32(-2x)sen x

limx→0-1+1+0/1 sen (0-) =2/0-= -∞
limx→0+1+1+0 sen(0∓) =2/0∓= +∞

91) limx→0ln(1+x2 cosx- e2
limx→0 2x1+ x2 –sen x- ex
limx→02x-(1+x2) (senx+ ex)
2(0)-(1+0)(0+e0) =0-1=092) limx→∞lnxx
limx→∞1x1xx1/2 = 2x1/2= 2∞=0

93) limx→∞ 2x2-15x2+3x
limx→∞4x10x+3 =410=25

94) limx→∞x lnxx2+1limx→∞lnx+x1x2x
limx→∞lnx+ 12x
limx→∞1x2 = limx→∞12x =1∞=0

95) limx→a2a3x- x4 . - a3a2x a-4ax3
limx→a122a3x-x4.-122a3 -4x3- a13a2 x-2/3(a2)-14 ax3 -34.(3ax2 )
12a4 -12.2a3-4a3 -a3a3 -2/3.(a2)-14 a4 --34.(3a3 )
-a-a3-34= -4a3-34 =169a96) limx→0xcotx
limx→0x.cosxsen x= limx→0cosx-xsenxcos x
cos0-0(0)cos (0)= 1-0 1=1

97) limx→0x3+3x+5senx-5x
limx→0x4+3x2+5x-5senxx sen x
limx→04x3+ 6x+5-5cosx sen x+xcosx
limx→012x2+ 6+5 sen xcosx+cosx+x (-senx)
0+6+5(0)1+1-0=62=3
tracking img